On overview of family knowledge on fish consumption in avoiding stunting in Meuraxa Sub-District of Banda Aceh municipality - Neti Hartaty; Rini Mastura (Dentistry Faculty, 2021)
ABSTRACT Approximately 37% or 9 million Indonesian children under five suffer from stunting.Although the prevalence of stunting under five tended to decline in 2013-2018 from 37.2% to 30.8%,stunting remains a top priority in the problem of improving Indonesia's nutrition for 2018-2024. Theresearch objective was to describe the family's knowledge of fish consumption in preventing stunting inMeuraxa District, Banda Aceh City. The descriptive exploratory nature of this type of research is evident.The research design was cross-sectional, with frequency distribution data being analyzed. Thepopulation for this study was made up of families with children ranging in age from one to five years.With 101 respondents, the sampling technique used was nonprobability sampling with a purposivesampling method. The data collection technique was carried out using a questionnaire, with guidedinterviews conducted via telephone. The results showed that as many as 51 (50.50%) respondents werecategorized as having good knowledge, 35 (36.65%) respondents were categorized as having sufficientknowledge. As many as 15 (14.85%) were classified as having less knowledge. It is recommended thathealth workers conduct and provide education about the importance of eating fish to prevent stuntingfor increased knowledge and application in the family. KEYWORDS: Fish consumption, Family knowledge, Stunting